Validity and reliability of GoJump photoelectric cells for estimating vertical jump height - Chen, X.; Mu, X. (Science & Sports, 2025)
Aims This study evaluated the validity and reliability of the GoJump system, a photoelectric cell-based device, for estimating vertical jump height.